Pengembangan Aspek Motorik Kasar Anak Usia Dini Melalui Permainan “Arsitek Cilik” (4-5 Tahun) - Arneta Widia; Dhiva Sahillah Saragih; Nur Zakiyah; Nur Hairani Siregar (Universitas Muhammadiyah Bandung, 2024)
This research focuses on the gross motor development of early childhood, particularly in the age range of 4-5 years, through the utilization of the